(untitled) (Journal of Bangladesh Institute of Planners, 2020)
The structure of the industrial sectors of a region is a driving factor to explain the growth of a region’s economy. In Bangladesh, spatial variation in economic growth exists among different regions. A primary factor in this variation is the economic structure of the region, which can be characterized by basic and non-basic sectors. Economic base theory helps to understand how data can be used to study the economic development process and evaluate alternating development strategies. The aim of the study, thus, is to identify the basic and non-basic sectors using economic base theory and to explore the short-run regional economic structure in selected districts. Data of selected districts from economic census, 2003, and 2013 has been analyzed for thirteen sectors. The comparative analysis of the selected districts reveals that all of the districts except Bandarban are becoming economically weak during the timeframe. In contrast, Bhola district is in economic malaise relative to the other districts. The lagging behind the Transport, Storage, and Communication sector triggers to the disadvantaged economic condition for all the districts during the timeframe. The findings of this study would act as a reference for regional planners to allocate resources in different economic sectors of these districts. JBIP, Vol. 13, 2020 (Printed in June 2021), pp. 17-28